PERENCANAAN STRATEGIS PENGEMBANGAN SUMBER DAYA MANUSIA BERBASIS KOMPETENSI: (Studi pada Badan Kepegawaian dan Pengembangan SDM Kabupaten Kebumen) - Nur Halim Rasyid (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
The Regional Government of Kebumen Regency through BKPSDM is tasked with developing apparatus resources within the scope of local government. In 2021, planning is carried out regarding the simplification of the bureaucracy which has an impact on the elimination of one level of structural positions that are converted into functional ones to be implemented in 2022. The analysis was carried out top down using the ABC theory of Strategic Planning and bottom up analysis using KSAO's personal competence theory. In order to find out the phenomena that occur, the authors apply qualitative research methods with a descriptive approach. The sources of research data obtained by the author through interviews, observations and analysis of documents related to the research topic. The results of research conducted based on the theory of ABC of Strategic Planning, it is necessary to make adjustments to the target of increasing the competence of the apparatus and making rules related to the changing work system. In the KSAO's personal competence section, it was found that there were different needs in the knowledge dimension for employees who experienced bureaucratic simplification. In the dimensions of skills and abilit